Antibacterial Effect of Dihydromyricetin on Specific Spoilage Organisms of Hybrid Grouper - Wenbo Huang; Jing Xie (Journal of Food Quality)
This study aimed to investigate the mechanism of antibacterial activity level inhibition of dihydromyricetin (DMY) against specific spoilage bacteria of grouper. Firstly, the specific spoilage bacteria of grouper in the cold storage process are Pseudomonas antarctica (P. antarctica), which are selected by calculating the spoilage metabolite yield factor. It was determined that the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of DMY against grouper spoilage bacteria were 2.0 mg/mL and 6.4 mg/mL, respectively. DMY was added to the matrix of chitosan and sodium alginate, and DMY emulsions of different concentrations (0 MIC, 1 MIC, 2 MIC, 4 MIC) were prepared and characterized by differential calorimetry methods. Through analyzing cell permeability, enzyme activity, and images of the confocal laser scanning microscope (CLSM), we further studied the antibacterial mechanism of DMY emulsion on specific spoilage bacteria. The results showed that, with the increase of DMY concentration in the treatment group, the leakage of nucleic acid and protein increased significantly, the activity of ATPase and three critical enzymes in the Embden-Meyerhof-Parnas (EMP) pathway decreased significantly, and the activity of AKPase did not decrease significantly, . The metabolic activity and viability are reduced considerably. Analysis of the above results shows that DMY inhibits the growth and reproduction of P. antarctica by interfering with the metabolic activity of bacteria and destroying the function of bacterial cell membranes but has no inhibitory effect on the activity of AKPase. This study proves that DMY could be an effective and natural antibacterial agent against specific spoilage bacteria in aquatic products.